Supervisi Kepala Sekolah Terhadap Kinerja Guru SD Negeri 219 Bengkulu Utara Untuk Meningkatkan Kualitas Pembelajaran - Mugiyono, Mugiyono (JPT : Jurnal Pendidikan Tematik, 2021)
This research was conducted to improve the quality of learning in the classroom. The data obtained in this research is from without giving treatment to the variables studied. So this research is included in the ex post facto research. The subjects in the study were all 12 teachers of SD Negeri 219 Bengkulu Utara, totaling 12 people. Data collection techniques using instruments and observation. Collecting data through a questionnaire instrument to obtain teacher performance data through the supervision of the principal, while data collection is through observation to obtain data on the quality of learning in class. Descriptive analysis is used to analyze data by describing the data that has been collected. The results of the research on the implementation of principal supervision on the performance of teachers at SD Negeri 219 Bengkulu Utara for the 2016/2017 academic year obtained a score of 882 with a percentage of 89.6% which was included in the Good category. While the results of research on the quality of learning in the classroom obtained a value of 1.316 with a percentage of 85.6% which is included in the Good category.